Bioprospecting of Ribosomally Synthesized and Post-translationally Modified Peptides Through Genome Characterization of a Novel Probiotic Lactiplantibacillus plantarum UTNGt21A Strain: A Promising Natural Antimicrobials Factory - Tenea, Gabriela N.; Ascanta, Pamela (Frontiers in Microbiology, 2022)
The present work describes the genome sequencing and characterization of a novel Lactiplantibacillus plantarum strain assigned UTNGt21A isolated from wild Solanum quitoense (L.) fruits. In silico analysis has led to identifying a wide range of biosynthetic gene clusters (BGCs) and metabolic compounds. The genome had a total of 3,558,611 bp with GC of 43.96%, harboring 3449 protein-coding genes, among which 3209 were assigned by the EggNOG database, and 240 hypothetical proteins have no match in the BLASTN database. It also contains 68 tRNAs, 1 23S rRNA, 1 16S rRNA, 6 5S rRNA, and 1 tmRNA. In addition, no acquired resistance genes nor virulence and pathogenic factors were predicted, indicating that UTNGt21A is a safe strain. Three areas of interest (AOI) consisting of multiple genes encoding for bacteriocins and ABC transporters were predicted with BAGEL4, while eight secondary metabolite regions were predicted with the antiSMASH web tool. GutSMASH analysis predicted one metabolic gene cluster (MGC) type pyruvate2acetate-formate, a primary metabolite region essential for anaerobe growth. Several lanthipeptides and non-ribosomal peptide synthase (NRPS) clusters were detected in the UTNGt21A but not the reference genomes, suggesting that their genome diversity might be linked to its niche-specific lineage and adaptation to a specific environment. Moreover, the application of a targeted genome mining tool (RiPPMiner) uncovered a diverse arsenal of important antimicrobial molecules such as lanthipeptides. Furthermore, in vitro analysis indicated that the crude extract (CE) of UTNGt21A exerted a wide spectrum of inhibition against several pathogens. The results indicated that the possible peptide-protein extract (PC) from UTNGt21A induces morphological and ultrastructural changes of Salmonella enterica subsp. enterica ATCC51741, compatible with its inhibitory potential. Genome characterization is the basis for further in vitro and in vivo studies to explore their use as antimicrobial producers or probiotic strains.